KUALITAS ILABULO MENGGUNAKAN TEPUNG SAGU DENGAN LEVEL YANG BERBEDA - Nupulo, Nindi; Kalele, J.A.D.; Sembor, S.M.; Lontaan, N.N (ZOOTEC, 2020)
THE QUALITY OF ILABULO USES SAGO FLOUR WITH DIFFERENT LEVELS. The study aims to evaluate the use of native chicken and starch   on   physical   and   organoleptic of ilabulo foods. This study was conducted using a complete random design (CRD), with four treatments: p1 (50 grams) p2 (100 grams) p3 (150 grams) p4 (200 grams) and five replication. Data was analyzed using anova (analysis of variance). Based on the results of data analysis that the variable of water holding capacity, moisture, flavor and taste showed non-significant differences while pH, the color, texture showed significant differences. It can be concluded that the use native chicken meat and sago flour of 100-200 grams to ilabulo food could be accepted by panelist.Keywords: native chicken, sago, ilabulo